Capecitabine versus S-1 as adjuvant chemotherapy for patients with stage III colorectal cancer (JCOG0910): an open-label, non-inferiority, randomised, phase 3, multicentre trial. (January 2018) - Hamaguchi, Tetsuya; Shimada, Yasuhiro; Mizusawa, Junki; Kinugasa, Yusuke; Kanemitsu, Yukihide; Ohue, Masayuki; Fujii, Shoichi; Takiguchi, Nobuhiro; Yatsuoka, Toshimasa; Takii, Yasumasa; Ojima, Hitoshi; Masuko, Hiroyuki; et al.
Summary: Background: Adjuvant chemotherapy with oral fluoropyrimidine alone after D3/D2 lymph node dissection improves disease-free survival and overall survival in patients with stage III colon cancer. Adjuvant S-1 has been shown to be non-inferior to uracil and tegafur plus leucovorin in terms of disease-free survival. This study aims to confirm the non-inferiority of S-1 compared with capecitabine as adjuvant treatment in patients with stage III colorectal cancer. Methods: This study was an open-label, non-inferiority, randomised, phase 3, multicentre trial done in 56 Japanese centres to assess the non-inferiority of S-1 to capecitabine as adjuvant chemotherapy. Eligible patients were aged 20–80 years with stage III colorectal adenocarcinoma, as defined by the presence of an inferior margin of the primary tumour above the peritoneal reflection; R0 resection; and colectomy with D3 or D2 lymph node dissection. Patients were randomly assigned (1:1) to receive eight courses of capecitabine (1250 mg/m 2 orally twice daily, days 1–14, every 21 days) or four courses of S-1 (40 mg/m 2 orally twice daily, days 1–28, every 42 days). Randomisation was done via phone call, fax, or web-based systems to the Japan Clinical Oncology Group Data Center and used a minimisation method with a random component adjusted by institution, tumour location (colon vs rectosigmoid and upper rectum), number of positive lymph node metastases (≤3 vs ≥4), and surgical technique (conventional vs non-touch isolation). The primary endpoint was disease-free survival with a non-inferiority margin for the hazard ratio (HR) set at 1·24, analysed by intention to treat. This trial was registered with UMIN Clinical Trial Registry, number UMIN000003272. Findings: Between March 1, 2010, and Aug 23, 2013, 1564 patients were randomly assigned to capecitabine (n=782) or S-1 (n=782), all of whom were included in the efficacy analysis; 777 patients in the capecitabine group and 768 in the S-1 group were included in the safety analysis. At the prespecified second interim analysis after final accrual, 258 (48%) of 535 required events were reported, and the Data and Safety Monitoring Committee recommended early publication because S-1 could not show non-inferiority compared with capecitabine for disease-free survival. With a median follow-up of 23·7 months (IQR 14·1–35·2), 3-year disease-free survival was 82·0% (95% CI 78·5–85·0) for the capecitabine group and 77·9% (74·1–81·1) for the S-1 group (HR 1·23, 99·05% CI 0·89–1·70; one-sided pnon-inferiority =0·46). The most frequent grade 3 or higher adverse events in the capecitabine group were hand–foot skin reactions (123 [16%] of 777 patients), and in the S-1 group were diarrhoea (64 [8%] of 768 patients) and neutropenia (61 [8%]). There was one (<1%) treatment-related death in each group. Interpretation: Adjuvant capecitabine remains one of the standard treatments for stage III colorectal cancer in Japan; S-1 is not recommended. Funding: National Cancer Center and Ministry of Health, Labour and Welfare of Japan.